2005
DOI: 10.1074/mcp.m400207-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation-related CD147-CD98 Complex

Abstract: Cell surface CD147 protein promotes production of matrix metalloproteinases and hyaluronan, associates with monocarboxylate transporters and integrins, and is involved in reproductive, neural, inflammatory, and tumor functions. Here we combined covalent cross-linking, mass spectrometric protein identification, and co-immunoprecipitation to show selective CD147 association with three major types of transporters (CD98 heavy chain (CD98hc)-L-type amino acid transporter, ASCT2, and monocarboxylate transporters) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
149
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(157 citation statements)
references
References 55 publications
8
149
0
Order By: Relevance
“…The intracellular glutamine supply is maintained via the intracellular Na + -dependent amino acid transporter ASCT2 that helps facilitate LAT1 function. The interplay between LAT1, ASCT2, and 4F2hc is thought to be important in controlling cancer cell metabolism [40]. For example, co-expression of LAT1 with ASCT2 has been shown in lung cancer, and this co-expression, but not the sole expression of LAT1 or ASCT2, is strongly related to prognosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular glutamine supply is maintained via the intracellular Na + -dependent amino acid transporter ASCT2 that helps facilitate LAT1 function. The interplay between LAT1, ASCT2, and 4F2hc is thought to be important in controlling cancer cell metabolism [40]. For example, co-expression of LAT1 with ASCT2 has been shown in lung cancer, and this co-expression, but not the sole expression of LAT1 or ASCT2, is strongly related to prognosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…46,47 On the other hand, the MCT1-CD147 complex is known to behave as a scaffold for other proteins involved in cell migration and invasion. 48 The composition of these supercomplexes is cell type-dependent and could logically be influenced by the cell environment and MCT1 expression and activity (conformation change).…”
Section: Discussionmentioning
confidence: 99%
“…MCT activity is also fundamental to the "Warburg effect" (Warburg, 1956), a glycolytic phenotype that is common to most malignant cancers and associated with resistance to therapies (Gatenby and Gillies, 2004;Koukourakis et al, 2006;Tredan et al, 2007). MCT-emmprin interactions have been demonstrated in human breast carcinoma cells (Gallagher et al, 2007;Xu and Hemler, 2005).…”
Section: Hyaluronan Cd44 and Emmprinmentioning
confidence: 99%
“…Interestingly, another common marker for cancer stem-like cells is EpCAM, also known as ESA (Al-Hajj et al, 2003;Dalerba et al, 2007b;Li et al, 2007a). EpCAM is a binding partner of emmprin (Xu and Hemler, 2005), implying that emmprin may also be associated with cancer stem-like cells. Moreover, it has been observed that breast carcinoma cells that express both CD44 and EpCAM are more malignant than cells expressing CD44 but not EpCAM (Al-Hajj et al, 2003).…”
Section: Regulation Of Cancer Stem Cell Properties By Hyaluronan Andmentioning
confidence: 99%